Carbon Accounting in Local-Scale Land Use and Land Cover Change - Goh, Jia Chen Judy (Consilience, 2017)
Complex land use and land cover change (LULCC) processes modify ecosystems’ ability to store and sequester carbon and regulate the climate, resulting in thermally uncomfortable climates and even more carbon emissions in an unchecked cycle. The value of potential loss of such climate ecosystem services remains understudied in urbanization planning and development. Using ecosystem modeling, this research quantifies potential changes of carbon storage and sequestration for a case of future LULCC in a tropical country by building an initial baseline carbon account of the existing forest. This study looked at a unique case of planned local-scale LULCC in Singapore where a secondary forest, Punggol Forest, is slated for conversion into a mixed-use residential neighborhood, Punggol Eco-Town. Carbon accounting is conducted to determine the carbon footprint of the LULCC, specifically for carbon storage and rate of carbon sequestration, using a sampled tree inventory with primary data collection. The results suggest that considerations of urban tree species selection in urban forestry are important in planning in order to reduce loss climate ecosystem services due to development. It is also a first step in using urban forestry tools for carbon accounting in decision-making for urban planning.